Soil-fertility constraints in different physiographic units in aridic areas of Bathinda, Punjab - SOOD, ANIL; CHHIBBA, I M; VERMA, V K; SHARMA, P K; NAYYAR, V K (The Indian Journal of Agricultural Sciences, 2014)
A study was carried out during 1997-99 to assess the soil-fertility status of 2 physiographic units, viz alluvial plain (AP) and sand dunes (SD), which were identified in Talwandi Saba tehsil in Bathinda district of Punjab, based on the interpretation of aerial photographs and satellite data. Surface soil (0-15 cm) samples from 200 sites, selected randomly based on the physiography, soil and land use, were collected and analysed for important soil properties and available nutrient contents. Index leaf samples of upland cotton (Gossypium hirsutum L.) were also collected from the same fields and analysed for total nutrient contents. The soils of the area were alkaline (PH 7.92-9.66), had low to high soluble salts (Ee 0.28-1.05 dS/m) and low to medium organic carbon (0.14Â·0.60%). All the samples tested low in available N (50.6161.3 kg/ha). About 28, 33 and 39% samples had low, medium and high available P respectively. Available K content in soils ranged from 137 to 515 kg/ha, with a mean of 244 kg/ha, Soil test indicated deficiencies of Zn and Fe in 62 and 90% samples, respectively, compared to only 5 and 3 % revealed by plant analysis, indicating a need to redefine critical levels of micronutrients for cotton.